Caso de estudio Colegio Peruano Chino Juan XXIII: influencia de los factores educativos y sociales en el perfil emprendedor de los alumnos - Delgadillo Azabache, Miguel Augusto (2022)
The present investigation is based on the factors that influence the entrepreneurship of the 4th and 5th year students of the secondary level of the Colegio Peruano Chino Juan XXIII, for which a quantitative study has been carried out through the Likert scale questionnaire instrument. This research proposes to analyze which of the analyzed factors, educational factor or social factor, has the greatest influence on the entrepreneurial profile of the students of the school in question, for which the IBM SPSS Statistics tool has been used, which will provide us with the necessary results to carry out the corresponding analysis. In the next chapters, the problem of entrepreneurship in the country will be developed and how it has developed over the years. The theoretical framework will give us a backup of how these variables have been obtained and that other research has been carried out within the framework of entrepreneurship in the school stage. Likewise, with the development of our research, we will analyze which dimensions are decisive in the study factors. Finally, the investigation will be concluded with the conclusions and recommendations on the results obtained that will give us a greater scope.